Meeting between the Prime Minister and representatives of the Trades Union Congress General Council Special Industrial Committee and Miners' Federation of Great Britain (6.15 pm) (verbatim report) : (1926/04/29) - Trades Union Congress. General Council. Special Industrial Committee ; Baldwin, Stanley Baldwin, Earl, 1867-1947 ; Miners' Federation of Great Britain
29 April 1926